The Effect of Retention Time and Initial Concentration of Ammonia on Biological Treatment for Reducing Ammonia Content in Wastewater - Muhammad Faizal (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
As we know that, urea fertilizer Industry is one of important industries for supporting food consumption. But, in manufacturing process, this industry produces a wastewater containing ammonia. Before ammonia rejected to environment, it should be treated. Biological process at perforated plate with foam as attachment media and addition of ammonia degrading isolate is used as an alternative treatment with observing the effect of residence time and initial concentration of NH3-N on its pollutant degradation. From this research, biological process occur with residence time of 63 to 250 minutes and range of initial concentration from NH3-N 276 to 530 mg/L. The results are as follows: removal of ammonia of 20.92 – 56.52%, COD of 48.46 – 74.52 %, and TKN of 17.69 – 44.89 %.